2020
DOI: 10.3390/su12166530
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Fragility Assessment of Columns in a Piloti-Type Building Retrofitted with Additional Shear Walls

Abstract: This study evaluated the influence of additional shear walls, constructed on the first floor, as strengthening methods for a piloti-type building subjected to earthquake loadings. Piloti-type buildings are commonly designed as urban structures in many cities of South Korea. The existence of just columns on the first floor of the building is a feature that is advantageous from an architectural viewpoint, and yet has potential structural disadvantages. Such columns usually exhibit shear–axial failure, due to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…As a result, experiments have been performed to better apprehend the structural conduct of shear partitions under distinctive loading situations and instances. The seismic conduct of prefabricated strengthened shear partitions with vertical joints was investigated by Zhang and Wang [17,18], in which shear walls were constructed in a pilot building. Coccia et al [19] studied the overall seismic performance of masonry partitions modified with vertical FRP stiffeners and found that conventional methods of seismic strengthening of masonry partitions have an impact on the seismic performance of the components.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, experiments have been performed to better apprehend the structural conduct of shear partitions under distinctive loading situations and instances. The seismic conduct of prefabricated strengthened shear partitions with vertical joints was investigated by Zhang and Wang [17,18], in which shear walls were constructed in a pilot building. Coccia et al [19] studied the overall seismic performance of masonry partitions modified with vertical FRP stiffeners and found that conventional methods of seismic strengthening of masonry partitions have an impact on the seismic performance of the components.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research studies have been carried out to understand the structural behaviour of shear walls under different load cases and conditions. Zhang and Wang [17] investigated the seismic performance of prefabricated reinforced masonry shear walls with vertical joint connections, while Dang-Vu et al [18] studied the seismic fragility assessment of columns in a piloti-type building retrofitted with additional shear walls. Coccia et al [19] reported the behaviour of masonry walls retrofitted with vertical FRP rebars, and their study showed that the conventional seismic retrofitting techniques on masonry walls influence the seismic performance of the element, which is typically modified in an out-of-plane bending behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…However, the seismic damage assessment on a regional level using a finite element (FE) analysis for individual building structures was not feasible because the FE-based simulation can be extremely time-consuming due to the individual analytical model's complexities (e.g., geometric effects and a large number of elements). Therefore, many previous studies presented the regional seismic damage assessment based on evaluated seismic performance using a single-degree-of-freedom (SDOF) structure [11][12][13][14][15][16]. For example, the HAZUS-MH earthquake model [14] was developed using the SDOF model for the regional seismic damage simulation.…”
Section: Introductionmentioning
confidence: 99%